Analisis Beban Kerja dan Lingkungan Kerja dalam Pencapaian Target pada Kinerja Karyawan Bank Jateng: Studi Kasus pada Bank Jateng Cabang Metro - Ratih Amalia Widhi Hapsari; Sari Listyorini; Hari Susanta Nugraha (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Employee performance is a key pillar in determining operational success and the quality of banking services. However, an unbalanced workload and a less-than-conducive work environment often trigger stress and reduce productivity. Therefore, this study aims to analyze the role of workload and the work environment in achieving employee performance targets at Bank Jateng Metro Branch. This study used a descriptive qualitative method, collecting data through observation, interviews, and documentation studies. The results show that proportional workload management—adjusted to the capacity and availability of human resources—has been proven to increase the effectiveness of optimal task completion. Furthermore, a conducive work environment, both physical and non-physical, significantly increases employee comfort and motivation. This study also identified variations in performance achievement between divisions influenced by job characteristics, task complexity, and the availability of supporting facilities. In conclusion, sustainable improvement in employee performance achievement depends heavily on balanced workload distribution, the creation of a supportive work environment, and the establishment of clear and measurable performance targets.